Innovative Transformation of Analog to Digital Direct Shear Test Tool Based on Microcontroller with Wireless Data Acquisition System - Maskur Efendi; Eko Setyawan (Universitas Islam Raden Rahmat, Malang, 2025)
Direct Shear Test (DST) is an important method for measuring soil shear strength in civil engineering applications. However, analog DST tools have limitations, such as low accuracy, low efficiency, and the need for manual data processing. This study aims to convert analog DST tools into digital ones using Arduino UNO R4 WiFi-based microcontroller technology and a wireless data acquisition system. This innovation replaces analog dial indicators with digital dial indicators to record shear force and horizontal displacement data automatically and in real-time. This system is designed to generate automatic test reports in the form of tables, graphs, and soil parameters, such as cohesion and angle of internal friction. The results show an accuracy rate of up to 90% compared to test results with commercial digital DST, better operational efficiency with only one operator, and a 30% reduction in testing time compared to using analog DST. With an implementation cost of less than 10% of commercial digital DST, this solution offers affordable modern testing technology for laboratories with limited budgets. This article discusses the technical design, hardware implementation, software development, and performance analysis of the resulting tool.